Patterns of community assembly in the developing chicken microbiome reveal rapid primary succession. Issue 9 (3rd March 2019) - Jurburg, Stephanie D.; Brouwer, Michael S. M.; Ceccarelli, Daniela; van der Goot, Jeanet; Jansman, Alfons J. M.; Bossers, Alex
Abstract: The fine‐scale temporal dynamics of the chicken gut microbiome are unexplored, but thought to be critical for chicken health and productivity. Here, we monitored the fecal microbiome of healthy chickens on days 1–7, 10, 14, 21, 28, and 35 after hatching, and performed 16S rRNA amplicon sequencing in order to obtain a high‐resolution census of the fecal microbiome over time. In the period studied, the fecal microbiomes of the developing chickens showed a linear‐log increase in community richness and consistent shifts in community composition. Three successional stages were detected: the first stage was dominated by vertically transmitted or rapidly colonizing taxa including Streptococcus and Escherichia/Shigella ; in the second stage beginning on day 4, these taxa were displaced by rapid‐growing taxa including Lachnospiraceae and Ruminococcus‐ like species variants; and in the third stage, starting on day 10, slow‐growing, specialist taxa including Candidatus Arthrobacter and Romboutsia were detected. The patterns of displacement and the previously reported ecological characteristics of many of the dominant taxa observed suggest that resource competition plays an important role in regulating successional dynamics in the developing chicken gut. We propose that the boundaries between successional stages (3–4 and 14–21 days after hatching) may be optimal times for microbiome interventions. Abstract : Here, we monitored the fecal microbiome of healthy chickens on days 1–7, 10, 14, 21, 28, and 35 after hatching, and performed 16S rRNA amplicon sequencing in order to obtain a high‐resolution census of the fecal microbiome over time. In the period studied, the fecal microbiomes of the developing chickens showed a linear‐log increase in community richness and consistent shifts in community composition. The patterns of displacement and the previously reported ecological characteristics of many of the dominant taxa observed suggest that resource competition plays an important role in regulating successional dynamics in the developing chicken gut.